THE EVALUATION OF SPECIAL EDUCATION COURSES IN TERMS OF EDUCATIONAL ATTAINMENTS OF PRE-SERVICE MATHEMATICS TEACHERS - (:unkn) unknown (My University, 2014)
Araştırmanın amacı, ilköğretim matematik öğretmen adaylarıyla gerçekleştirilen özel eğitim dersi kapsamında öğretmen adaylarının elde ettiği kazanımları belirlemektir. İlköğretim matematik öğretmen adaylarıyla kaynaştırmayla ilgili olarak öğretmen adaylarının bilgilendirilmesi ve bu dersin yansımalarının belirlenmesi bakımından çalışma önem taşımaktadır. Ayrıca çalışmada rol alan araştırmacılardan birinin kaynaştırma bir çocuğa sahip olması ve aynı zamanda araştırmacıların İlköğretim Anabilim Dalı İlköğretim matematik öğretmenliği Bilim Dalı'nda görev yapıyor olmalarının da çalışma açısından büyük önem taşıdığı düşünülmektedir. Bu sayede kaynaştırma konusunda bunu en yakından tecrübe etmiş bir kişinin yaşadığı sıkıntılar, zorluklar ve edilen mücadelelerin görülmesi ve özellikle de matematik alanında kaynaştırma öğrenciler için neler yapılabileceğinin belirlenmesi bakımından araştırma önemlidir ve alanyazına büyük katkı sağlayacağı düşünülmektedir. Araştırmada nicel veri toplama tekniklerinden "Tek grup öntest-sontest" deseni kullanılmıştır. Araştırma 38 öğretmen adayıyla gerçekleştirilmiştir. Araştırmada ele alınan problemlerin çözümüne yönelik iki farklı veri toplama aracından yararlanılmıştır. Bunlar "Kaynaştırma öğrencileri ile İlgili Temel Kavramları Bilme" (Form 1) formu ve "Kaynaştırma Öğrencileri ve Ailelerini Algılama ve Sorunlara Çözüm Getirebilme" (Form 2) formu" 'dur. Araştırmada gerçekleştirilen uygulamalar 2010-2011 akademik yılı güz döneminde, Özel Eğitim dersi kapsamında 14 hafta süresince yürütülmüştür. Araştırma kapsamında yapılan "Kaynaştırmayla ilgili temel kavramları bilme", "Kaynaştırma öğrencilerin yasal haklarının neler olduğunu bilme veya takip edebilme" "Kaynaştırma öğrencilerin aileleriyle empati kurma", "Gelecekte bir öğretmen veya bir okul idarecisi olarak sorunlara çözüm getirebilme", "Kendisini özel eğitim konusunda matematik alanında yeterli görme" becerilerini ve "Kaynaştırma öğrencileri algılama düzeyleri" ni arttırmıştır

The purpose of this research is to define the level of attainments acquired by elementary school pre-service mathematics teachers within the scope of special education lesson which was carried out with these teachers. This study is of importance in terms of informing pre-service teachers about mainstreaming within the scope of special education course carried out with primary mathematics pre-service teachers and determining the reflections of this course on the attitudes of pre-service teachers regarding the subject. Also, It is thought that one of the researchers who participated in this study has a mainstreamed child and at the same time they are working in the Primary Mathematics Teaching Department are important factors in terms of the study. With this, this study is important in terms of seeing the efforts, difficulties and troubles of someone who experienced closely things about mainstreaming subject and especially determining the things that can be done for mainstreamed students in the field of mathematics and it is thought that this study can make great contributions to the literature. The design of ‘pretest-posttest with single group’ was used among quantitative data collection tools in the present study. This study was carried out with 38 pre-service teachers. Two different data collection instruments were used for the solutions of the problems discussed in this study. These instruments are ‘Knowing the Basic Concepts about Mainstreaming Students (Form 1)’ and ‘Perceiving Mainstreaming Students and their Families and the Ability to Find Solutions’ (Form2)’ forms. Research applications were carried out during 14 weeks in the fall semester of 2010-2011 academic years within the scope of special education course. This study increased pre-service teachers’ abilities of “Knowing basic concepts regarding mainstreaming”, “The ability of knowing the legal rights of mainstreaming students and the ability to asking for these rights”, “The ability of feeling empathy with the families of mainstreaming students”, “The ability of finding solutions to problems as future teacher or school administrator ”, “The ability of feeling self-sufficient about special needs education in the field of mathematics” and “Types of perceiving mainstreaming students”
ÖZEL EĞİTİM DERSLERİNİN İLKÖĞRETİM MATEMATİK ÖĞRETMEN ADAYLARININ KAZANIMLARI BAKIMINDAN DEĞERLENDİRİLMESİ